2020
DOI: 10.1038/s41598-020-64663-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Endogenous Control Reference Genes for Studies on Type 1 or Type 2 Endometrial Cancer

Abstract: A panel of 32 candidate reference genes was used to identify the most stable genes for gene normalisation in quantitative RT-PCR studies using endometrial biopsies obtained from women with endometrial cancer (type 1 or type 2) and without cancer (controls). RNA from the biopsies was isolated, examined for purity and quality, and then reverse transcribed into cDNA before being subjected to real-time qRT-PCR analysis in triplicate within the TaqMan gene Expression Assay kit. The most 'stable' endogenous control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…PSMC4 and PSMC5 contribute to prostate tumorigenesis [ 35 ]. Additionally, PSMC4 was identified as one of the best biomarkers for endometrial cancer [ 36 ], and risk model construction revealed that it is also a prognostic marker for the same type of cancer [ 37 ]. PSMC5 acts as a novel regulator and is involved in the extracellular signal-regulated kinase 1/2 signaling pathway [ 38 ], and it was observed to have a relatively higher cytoplasmic expression pattern in most cancer types [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSMC4 and PSMC5 contribute to prostate tumorigenesis [ 35 ]. Additionally, PSMC4 was identified as one of the best biomarkers for endometrial cancer [ 36 ], and risk model construction revealed that it is also a prognostic marker for the same type of cancer [ 37 ]. PSMC5 acts as a novel regulator and is involved in the extracellular signal-regulated kinase 1/2 signaling pathway [ 38 ], and it was observed to have a relatively higher cytoplasmic expression pattern in most cancer types [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…MRPs have a significant effect in female-specific cancers. MRPL19 is one of the internal reference genes for type I or II endometrial cancers and the expression level of MRPL46 had the greatest influence on the prognosis of ovarian cancer [ 19 , 20 , 49 ]. Overexpression of MRPS18-B (MRPS18-2) leads to the epithelial cells that acquire a higher migration ability to transform as mesenchymal cell (EMT).…”
Section: Mrps Associated With Cancersmentioning
confidence: 99%
“…Endometrial cancers [19,20], Diffuse non-Hodgkin lymphoma [21], Melanoma [22] MRPL21 bL21m Acute myeloid leukemia [23] ↑…”
Section: Mrpl19 Bl19mmentioning
confidence: 99%
“…mRNA is a single-stranded molecule of RNA that is complementary to the genetic sequence of a gene and has been commonly used as a biomarker for early detection and treatment of cancer due to its humoral stability and biological regulatory function. It is usually quantitatively detected using quantitative reverse transcription-polymerase chain reaction (qRT-PCR) [35][36][37]. Although qRT-PCR is a very sensitive method, it is timeconsuming and requires heavy instruments for the associated thermocycling reactions.…”
Section: Messenger Rna (Mrna)mentioning
confidence: 99%